Tele-Oncology And The Covid-19 Phenomenon: A Narrative Review Of Core Findings, Opportunities, And Road Ahead (The Review of Diabetic Studies, 2025)
BackgroundThe global COVID-19 phenomenon initiated an unexpected revolution in oncology care services by presenting telehealth via the internet and telephone, which has become a standardized method. It also ensures ongoing cancer care delivery to safeguard high-risk patients by focusing on the threat of infection, particularly for those affected by carcinoma. Technology-enabled cancer treatment rapidly developed a key intervention to maintain therapeutic guidelines and challenges in healthcare delivery; yet, its fast-tracked adoption has led to visible long-lasting disparities, virtual health inequities, and functioning boundaries within well-being schemes universally. Also, this shift emphasized substantial limitations in digital health awareness and highlighted the demand for enduring, accessible technological implementation in oncology for the upcoming health delivery.ObjectiveThis narrative review delivers an essential and complete evaluation of the growth of tele-oncology during the COVID-19 surges. This study reveals and investigates significant factors of telehealth application, produces recent research on cancer experimental results and patient experiences in oncology care, comprehensively inspects chronic challenges comprising individuals associated with health equity, strategy, and framework, and recommends research-informed strategies for durable, patient-centered inclusion of digital oncology care into prospective people with malignancies. In addition, this paper highlights the engagement of regulatory bodies, clinical leaders, and tech-based innovators in building infrastructure that supports telemedicine and impactful digital health outcomes.MethodsA literature review was characterized by using PubMed, Scopus, and Google Scholar databases. The manuscript from 2015 to 2024 was studied, with detailed consideration to carcinoma, telehealth, virtual health, and health justice. We conducted about 47 referenced articles, policy analyses, and formal guidelines, which were categorically interpreted to cite core understandings into the adoption, execution, findings, and opportunities in teleconsultation in carcinoma treatment. The urgency was specified to research tackling demographically diverse groups and diverse care circumstances to present a broad analysis.ResultsTelehealth in oncology has shown a considerable role in continuity in malignancy treatment in improving patient confidence via increasing access to neoplastic disease care services, mainly between neglected and remote populations. However, major obstacles remain; digital health inequities, fragmented policies, inconsistent reimbursement structures, and infrastructural inadequacies continue to impede broader and more equitable implementation. Furthermore, the integration of emerging digital health technologies such as AI, machine learning, and remote monitoring systems, while promising, necessitates robust governance, validation, and alignment with existing clinical and regulatory frameworks in oncology.ConclusionTele-oncology holds transformative potential to reshape oncology cancer care delivery beyond the exigencies of the COVID-19 crisis. Realizing this potential requires dismantling systemic barriers, addressing the digital health divide, fostering digital health literacy, and embedding telemedicine within robust hybrid oncology care models supported by sustainable policy reforms, adequate reimbursement structures, and equitable infrastructure development. Prioritizing health equity will be essential in these efforts.